2009
DOI: 10.1111/j.1467-8683.2009.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Financing Constraints, Ownership Control, and Cross‐Border M&As: Evidence from Nine East Asian Economies

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: This study distinguishes between the effects of financial constraint determinants on cross-border mergers and acquisitions (M&As) and domestic M&As for all takeover bids announced in nine East Asian economies from 1998 to 2005. Research Findings/Insights: The results of logistic regressions verify that the extent of stock market and governance developments improves corporate financing conditions and subsequently encourages cross-border M&As in East Asia. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 74 publications
2
52
0
2
Order By: Relevance
“…For example, Japanese outward M&A purchases have declined in 1990s and outward investments by Asian countries reported declining trend due to 1997 currency crisis (Kang & Johansson, 2000). While supporting this line, Chen et al (2009) suggested that firm investment decisions not only influenced by internal funds (e.g., deep pockets, arranging funds from subsidiaries), but also affected by outside investors who participate in capital markets. Hence, these external markets become imperfect and then not accessible (or, accessible at high transaction costs) for firm managers due to major uncertainties in macroeconomic policies such as legal codes, contract enforcement and information disclosure systems, which in turn affect the financial development and economic growth of the given country (Beck, Demirgüç-Kunt, & Levine, 2001;Forssbaeck & Oxelheim, 2011).…”
Section: [Insert Figure 3]mentioning
confidence: 84%
See 4 more Smart Citations
“…For example, Japanese outward M&A purchases have declined in 1990s and outward investments by Asian countries reported declining trend due to 1997 currency crisis (Kang & Johansson, 2000). While supporting this line, Chen et al (2009) suggested that firm investment decisions not only influenced by internal funds (e.g., deep pockets, arranging funds from subsidiaries), but also affected by outside investors who participate in capital markets. Hence, these external markets become imperfect and then not accessible (or, accessible at high transaction costs) for firm managers due to major uncertainties in macroeconomic policies such as legal codes, contract enforcement and information disclosure systems, which in turn affect the financial development and economic growth of the given country (Beck, Demirgüç-Kunt, & Levine, 2001;Forssbaeck & Oxelheim, 2011).…”
Section: [Insert Figure 3]mentioning
confidence: 84%
“…We also noticed growing research interest on CB-M&As in other emerging and Asian markets (Ang, 2008;Chen et al 2009;Fedderke & Romm, 2006;Pablo, 2009;Wang, 2013). In the early study, Vasconcellos et al (1990) investigated the determinants of CB-M&As involving US firms.…”
Section: [Insert Figure 3]mentioning
confidence: 99%
See 3 more Smart Citations